2017
DOI: 10.5761/atcs.oa.16-00219
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different BMI on Blood Loss and Transfusions in Chinese Patients Undergoing Coronary Artery Bypass Grafting

Abstract: Objective: Blood loss is a predictor of outcomes after coronary artery bypass grafting (CABG). This study investigated the effects of body mass index (BMI) on blood loss, blood transfusion rate, and the variations in coagulation parameters of Chinese patients undergoing CABG. Methods: A total of 1007 Chinese patients who consecutively underwent isolated, primary CABG at Fuwai Hospital from January 1, 2013 to December 31, 2013 were included in this study. They were categorized by BMI into <24 kg/m 2 (low and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 30 publications
4
20
0
1
Order By: Relevance
“…Similar evidence derived from valvular and combined surgery (4). Obese patients require significantly lower rates of re-exploration for bleeding and allogenic blood products transfusions, which are, in turn, major determinants of lung impairment (13,15). Data from a multi-institutional perfusion database demonstrated, that a BMI in obese I category was associated with a 9.9% decrease in transfusion risk (P<0.05).…”
Section: Postoperative Complications In the Obese Patientmentioning
confidence: 71%
“…Similar evidence derived from valvular and combined surgery (4). Obese patients require significantly lower rates of re-exploration for bleeding and allogenic blood products transfusions, which are, in turn, major determinants of lung impairment (13,15). Data from a multi-institutional perfusion database demonstrated, that a BMI in obese I category was associated with a 9.9% decrease in transfusion risk (P<0.05).…”
Section: Postoperative Complications In the Obese Patientmentioning
confidence: 71%
“…[5] 13637 hastalık çalışmada obez ve morbid obez grupta daha az kanama ve kan ürünü kullanımı gerektiğini göstermişlerdir. Yine iki farklı çalışmada da, obez olgularda kanama komplikasyonu ve buna bağlı re-operasyon oranlarının daha az olduğu gösterilmiştir [15,18] . Pek çok çalışmada obezitenin daha az kanamayla ilişkisi gösterilmiş ve bunun nedeni olarak, mediastende biriken büyük miktardaki yağ dokusu ve yüksek intraabdominal basıncın, intratorasik basıncı arttırarak kanama alanlarında kompresyon etkisi yaratması, açıklık kazanmasa da obeziteye bağlı hiperkoagülopatik durum ve daha az hemodilüsyon gereksinimi olarak bildirilmiştir [5,[13][14][15]17,18] .…”
Section: Discussionunclassified
“…Conflicting reports regarding intraoperative blood loss in obese patients undergoing surgery in different settings have been documented. Bowditch et al reported that obese patients having hip replacement surgery bled more compared to patients with normal BMI [ 30 ], whereas Wang et al showed that obesity is a protective factor against the need to receive blood transfusion during coronary artery bypass surgery [ 31 ]. Our study showed that, although blood loss was higher in obese patients, no difference in transfusion rate occurred.…”
Section: Discussionmentioning
confidence: 99%